Headache patients in the emergency department of a Greek tertiary care hospital - Dermitzakis, Emmanouil V. (Springer Milan, 2009)
The aim of this study was to record the demographic and epidemiological data on adult patients with headache who attend the emergency department (ED) and the diagnoses that made by the neurologists in the ED of a tertiary care hospital in metropolitan Thessaloniki (Greece). In an open prospective study, demographic and epidemiological data were collected on all patients who reported headache (as chief complaint or not) and presented to the ED of Papageorgiou Hospital between August 2007 and July 2008. Headache patients accounted for 1.3% of all ED patients and for 15.5% of patients primarily referred to the ED neurologist. Tension type headache was the most frequent diagnosis, followed by secondary headaches and migraine. The large number of patients without final ED diagnosis and ward admission for further evaluation sheds a light on the immense workload of Greek ED physicians. Furthermore, we found evidence for the misuse of Emergency Medical Services by chronic headache patients. These findings indicate shortcomings in the pre-hospital (primary care) management of headache patients in the Greek National Health System to an extent unreported so far. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10194-009-0178-3) contains supplementary material, which is available to authorized users.